Speechlessness before history : empathic unsettlement in J.M. Coetzee’s age of iron and disgrace - Lim, Ariel Tabitha (2017)
Even before New Historicism, South African literature was already being read in its historical context because of the appalling, overbearing racism of the apartheid system. South African novels tended towards social realism, which allowed authors to condemn the apartheid system by describing its barbarity. The problem that social realism poses for white South African writers of conscience is that they risk colonising black experience in their representations of it. Afrikaner author J.M. Coetzee meets this challenge in his novels Age of Iron (1990), set during the peak of anti-apartheid violence, and Disgrace (1999), set in early post-apartheid conditions. By self-reflexively calling attention to the failure of language in representing racial violence and suffering in South Africa, the novels explore Dominick LaCapra’s concept of empathic unsettlement which “involves a kind of virtual experience through which one puts oneself in the other’s position while recognising the difference of that position” and therefore not claiming the other’s subject position or voice (78). Coetzee thus observes the ethical position and boundaries of a white writer witnessing black suffering speaking out against apartheid.